Tecnologias web aplicadas na Automação Industrial: utilização em um sistema de varredura aérea - Castelo Branco, Italo Rosse Alves (2021)
This work presents a web platform that supports the operation of an aereal volumetry and coal stock manegement system. This system is composed by a drone equipped with a LiDAR sensor for geometric mapping of stockpiles and a web application, responsable for monitoring and management of acquired information. The proposed web platform acts offering data persistence services, providing several measurements and implementing integration with other plant automation systems. It’s implementation was based on microservices architecture and data exchange is done by a integrated REST API. For performance evaluation, comparation between previosialy defined reference parameters and read, creation, update and exclusion data tests were performed. The results were promising, indicating acceptable code performance. Finally, contributions, improvement points and future works were discussed.